A thorough spectroscopic study of luminescent precursor solution of Y3Al5O12:Tb3+: influence of acetylacetone. Issue 48 (27th April 2016) - Potdevin, A.; Briois, V.; Caperaa, N.; Santilli, C. V.; Chadeyron, G.; Mahiou, R.
Abstract : Upon blue excitation, acac-modified solutions present significantly higher luminescence compared to unmodified ones due to the presence of pre-nuclei of YAG:Tb structure which is very interesting for using them for optical applications. Abstract : Undoped and Tb 3+ -doped precursor solutions of Y3 Al5 O12 (YAG) have been prepared by the sol–gel process using alkoxide precursors stabilized by a chelating agent: acetylacetone (acacH), with various complexation ratios R C = 0, 1, 2 and 3 defined as the ratio between [Al(OPr i )3 ] and [acacH]. Combining in situ UV-visible investigation of the hydrolysis process of these sols with X-ray diffraction study on the powders extracted after water addition to the sols, drying and subsequent heating, an optimal R C value has been determined. It leads to sols stable over a long period of time and resulting in a pure YAG phase. Structural and optical properties of Tb 3+ -doped precursor sols characterized by R C = 0 (as a reference for the influence of acacH) and R C = 1 (determined optimal value) were studied by means of X-ray Absorption Spectroscopy (XAS) and photoluminescence, respectively. Y K and Tb L3 edges XAS results show the presence of double heterometallic Y or Tb/Al alkoxides for the sol with R C = 1 involving pre-nuclei cluster with YAG structure. Emission and excitation spectra as well as decay curves were recorded and compared. Results revealed that the stabilized sol is much more efficient upon UV excitation than its unmodified counterpart thanks to an efficient energy transfer from acetylacetonate groups to active ions. Upon a 485 nm excitation, acac-modified samples remain the most efficient ones. It could be related to the dissimilar Tb local environments of the sols suggested by both UV-visible and photoluminescence excitation results.